Self-consistent coupling of DSMC method and SOLPS code for modeling tokamak particle exhaust. (4th May 2017) - Bonelli, F.; Varoutis, S.; Coster, D.; Day, C.; Zanino, R.
Abstract: In this work, an investigation of the neutral gas flow in the JET sub-divertor area is presented, with respect to the interaction between the plasma side and the pumping side. The edge plasma side is simulated with the SOLPS code, while the sub-divertor area is modeled by means of the direct simulation Monte Carlo (DSMC) method, which in the last few years has proved well able to describe rarefied, collisional flows in tokamak sub-divertor structures. Four different plasma scenarios have been selected, and for each of them a user-defined, iterative procedure between SOLPS and DSMC has been established, using the neutral flux as the key communication term between the two codes. The goal is to understand and quantify the mutual influence between the two regions in a self-consistent manner, that is to say, how the particle exhaust pumping system controls the upstream plasma conditions. Parametric studies of the flow conditions in the sub-divertor, including additional flow outlets and variations of the cryopump capture coefficient, have been performed as well, in order to understand their overall impact on the flow field. The DSMC analyses resulted in the calculation of both the macroscopic quantities—i.e. temperature, number density and pressure—and the recirculation fluxes towards the plasma chamber. The consistent values for the recirculation rates were found to be smaller than those according to the initial standard assumption made by SOLPS.